Effectiveness of education information concelling of knowledge women of age about cancer cancer and visual acetic acid inspection as early detection - Cut, Adeya Adella; Sitohang, Nur Asnah (Talenta Publisher, 2019)
Cervical cancer is cancer that occurs in the cervix , an area in the female reproductive organs which is the entrance to the uterus, located between the uterus and the intercourse or vagina. The main cause of cervical cancer is Human Papilloma Virus (HPV) infection. Cervical cancer usually attacks women aged 35-55 years. Visual Inspection with Acetic Acid (IVA) is a visual inspection of the cervix using vinegar with the eye to detect abnormalities after applying 3-5% vinegar. This community service aims to: (1) provide communication, education and information (IEC) about cervical cancer and the benefits of IVA Test, (2) conduct IVA Test, (3) measure the knowledge of women of childbearing age about cervical cancer and IVA test. Implemented at Klinik Bersalin Sari Medan (30 people). Data analysis using Wilcoxon test. The results of the activity obtained the majority of data aged 37-39 years (43.3%), Javanese (40%), Islamic religion (90%), first married age 21-23 years (43.3%), the number of births 3 times (30% ), the IVA test results are negative (90%), inflammation / cervicitis (10%). The knowledge before being given Information Education Communication (IEC) averaged = 14.57; SD = 3,633 and after being given IEC average = 23.60, SD = 1,589. Statistical test results obtained mean difference = 9.03 and P value = 0.001, it can be concluded that there is a significant influence of IEC on women of childbearing age knowledge about cervical cancer and IVA tests. It is recommended to midwives to socialize the benefits of IVA tests and carry them out as early detection of cervical cancer.